Pseudo-Roberts Syndrome: An Entity or Not?. (1st June 2022) - Salari, Behzad; Dehner, Louis P.
Abstract: Background: Roberts syndrome is a genetic disorder characterized by tetra-phocomelia with abnormalities of ESCO2. We report a male stillborn with tetra-phocomelia and no ESCO2 mutation. Case report: Pre- and post-natal imaging and autopsy findings included schizencephaly, phocomelia of four limbs, micrognathia, oligodactyly, and cardiopulmonary malformations. Microcephaly on pre-natal imaging was not confirmed by autopsy examination. Karyotype, prenatal chromosome microarray and ESCO2 gene testing were normal. Conclusion: Given the various skeletal anomalies found on autopsy and imaging evaluations, at least phenotypically, our case appeared to conform into Roberts syndrome spectrum. Since the infant did not have the mutation associated with this disorder, this infant could be labeled as the first report of a pseudo-Roberts syndrome because many of his phenotypic anomalies are characteristic of Roberts syndrome in absence of the ESCO2 gene mutation.